PENGARUH GREEN MARKETING TERHADAP PURCHASE DECISION YANG DIMEDIASI OLEH BRAND IMAGE (Studi pada AMDK Ades di Kota Denpasar) - Rayon, Yolanda Averina; Widagda, I Gst. Ngurah Jaya Agung (E-Jurnal Manajemen, 2021)
The emergence of the issue of environmental pollution demands that people become smarter in determining their choices in consuming products that are safe for the environment. Consumer perceptions arising from existence of green marketing activities are considered important because they can improve image of a company. This study aims to determine effect of green marketing on purchase decisions mediated by brand image. Research was conducted in Denpasar using AMDK Ades with117 respondents using purposive sampling method. Data collected through questionnaire via google forms and analyzed using path analysis and single test. The results indicate that green marketing has a positive and significant effect on purchase decisions. Green marketing has a positive and significant effect on brand image. Brand image has a positive and significant effect on purchase decisions. Brand image is able to mediate the effect of green marketing on purchase decisions on AMDK Ades products in Denpasar. Keywords: Green Marketing, Brand Image, Purchase Decision